2016
DOI: 10.1371/journal.pone.0152124
|View full text |Cite
|
Sign up to set email alerts
|

Early Impairment of Lung Mechanics in a Murine Model of Marfan Syndrome

Abstract: Early morbidity and mortality in patients with Marfan syndrome (MFS) -a connective tissue disease caused by mutations in fibrillin-1 gene- are mainly caused by aorta aneurysm and rupture. However, the increase in the life expectancy of MFS patients recently achieved by reparatory surgery promotes clinical manifestations in other organs. Although some studies have reported respiratory alterations in MFS, our knowledge of how this connective tissue disease modifies lung mechanics is scarce. Hence, we assessed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…Using pyramidal tips with k = 0.1 N/m we found that 7‐μm‐thick slices of acellular lung parenchyma ECM from rats exhibited heterogeneous E values, yet elastic measurements could clearly distinguish alveolar walls ( E ∼20 kPa) from the pleura ( E ∼50 kPa) (Luque et al, ). Slightly higher values were obtained in 12‐μm‐thick slices of acellular pulmonary tissue from mice (Figure A), which remained fairly constant with the age of the animal as shown in Figure B (Uriarte et al, ). Of note, AFM measurements revealed that elastin‐rich tissue structures such as the tunica media were 4‐fold stiffer than alveolar structures, and that this difference was maintained during aging (Figure A‐B), thereby illustrating the existence of homeostatic mechanisms that maintain physiologic tissue elasticities.…”
Section: Elastic Properties Of Decellularized Tissue Sectionsmentioning
confidence: 86%
“…Using pyramidal tips with k = 0.1 N/m we found that 7‐μm‐thick slices of acellular lung parenchyma ECM from rats exhibited heterogeneous E values, yet elastic measurements could clearly distinguish alveolar walls ( E ∼20 kPa) from the pleura ( E ∼50 kPa) (Luque et al, ). Slightly higher values were obtained in 12‐μm‐thick slices of acellular pulmonary tissue from mice (Figure A), which remained fairly constant with the age of the animal as shown in Figure B (Uriarte et al, ). Of note, AFM measurements revealed that elastin‐rich tissue structures such as the tunica media were 4‐fold stiffer than alveolar structures, and that this difference was maintained during aging (Figure A‐B), thereby illustrating the existence of homeostatic mechanisms that maintain physiologic tissue elasticities.…”
Section: Elastic Properties Of Decellularized Tissue Sectionsmentioning
confidence: 86%
“…Interestingly, AFM measurements of ECM scaffolds from decellularized thin sections of MFS lung revealed similar stiffness as WT. 48 We suspect the 3D organization of cellular and ECM components both contribute to the disruption of micromechanics in the MFS lung. Our results indicated that the apparent elastic modulus of the lung tissue, E lung , decreased dramatically with disease progression in MFS mice, consistent with the symptoms of obstructive lung disease.…”
Section: Discussionmentioning
confidence: 96%
“…Similar softening effects were recently reported in excised whole lungs from a mouse model of mild MFS, indicating a lower elastance in diseased mice accompanied by emphysema-like structure similar to our findings. 48 A mouse model of emphysema showed similar changes in the mechanics of the diseased lung, including a loss of elastin, increased hysteresis and non-linearity, and decreased load-bearing capacity. 22 Lung inflation testing has been performed to obtain a pressure-volume relationship that reflects the lung mechanical properties, using sequential images of lung inflation to assess micro- or macro-strain of the parenchyma tissue.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent expansion of AFM application to lung tissue has included several new studies on the mechanical properties of normal and decellularized lung tissue by AFM micro-indentation (Booth et al, 2012; Brown et al, 2013; Liu et al, 2010; Liu and Tschumperlin, 2011; Liu et al, 2016; Melo et al, 2014a; Meng et al, 2015; Shkumatov et al, 2015; Uriarte et al, 2016). Importantly, these new studies have begun to investigate anatomical variations in tissue mechanical properties, including comparisons of airways, vessels, pleura and parenchyma, but have also introduced substantial variation in tissue preparation (such as tissue decellularization), section thickness (10 to 1000 μm), and use of AFM tips with widely varying geometry and size.…”
Section: Introductionmentioning
confidence: 99%